Idiopathic Thrombocytopenic Purpura with Intracranial Haemorrhage and Menorrhagia - Das, Suchanda; Chowdhury, Bidhan Roy; Begum, Rokeya (Journal of Bangladesh College of Physicians and Surgeons, 2017)
A rare and life threatening complication of idiopathic thrombocytopenic purpura is intracranial hemorrhage ( ICH) and is the leading reported cause of death. The other important manifestation of ITP is menorrhagia. There are a variety of different causes of menorrhagia and gynecological evaluation is essential to tailor management to the individual patient to prevent unnecessary invasive procedure which may have limited effect. A 25 years old female para-2+0 presented with menorrhagia,severe excruciating headache,easy bruising, ecchymosis and petechialhemorrhage. After all investigation clinical evaluation it was diagnosed as a case of ITP with intracranial hemorrhage and menorrhagia. An intracranial hemorrhage is the most dreaded complication of ITP it is essential toprecede an early diagnosis, prompt and aggressive management and optimizing the management of acute menorrhagia remains of clinical importance due to life threatening nature of the condition. J Bangladesh Coll Phys Surg 2017; 35(2): 97-99